Nature and the environment in Amish life: nature, culture, and religion in everyday life - McConnell, David L. (Young Center books in Anabaptist and Pietist studies, 2018)
Growing up rural -- Working with nature -- Reconfiguring leisure and the outdoors -- The Amish as environmentalists